2016
DOI: 10.1136/tobaccocontrol-2015-052821
|View full text |Cite
|
Sign up to set email alerts
|

Phantom smoking among young adult bar patrons

Abstract: Objective To explore the prevalence and sociodemographic makeup of smokers who do not self-identify as smokers (ie, phantom smokers) compared with self-identifying smokers in a sample of bar-going young adults aged 18–30 years to more accurately assess young adult prevalence of smoking and inform cessation message targeting. Methods Cross-sectional surveys of smokers (n=3089) were conducted in randomly selected bars/nightclubs in seven US cities. Logistic regression models assessed associations between phant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
(50 reference statements)
1
14
0
Order By: Relevance
“…Recently, the term “phantom smoker” has emerged to characterize young adults who report smoking cigarettes, but do not self-identify as a smoker (Choi et al, 2011; Guillory, Lisha, Lee, & Ling, 2016). Among past 30-day young adult cigarette smokers recruited from 2012–2014 in U.S. bars and nightclubs, phantom smokers were 60% more likely to identify as social smokers than regular smokers (Guillory et al, 2016). Identifying as a social smoker seems to have utility for young adult smokers in dissociating their smoking behavior from the known harms of smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the term “phantom smoker” has emerged to characterize young adults who report smoking cigarettes, but do not self-identify as a smoker (Choi et al, 2011; Guillory, Lisha, Lee, & Ling, 2016). Among past 30-day young adult cigarette smokers recruited from 2012–2014 in U.S. bars and nightclubs, phantom smokers were 60% more likely to identify as social smokers than regular smokers (Guillory et al, 2016). Identifying as a social smoker seems to have utility for young adult smokers in dissociating their smoking behavior from the known harms of smoking.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, young adults frequently do not self-identify as Bsmokers,â nd thus may not tune-in to cessation messages or believe that evidence-based cessation programs fit them (Y. Choi et al 2011;Guillory et al 2016;Staten and Ridner 2007). As a result, young adults have not been the target of prevention, and there have been limited efforts targeting them for cessation.…”
Section: Prevescalation As a Research Gap And An Intervention Opportumentioning
confidence: 99%
“…These findings provide important contributions to the existing literature that has shown that these methods can be used to recruit LGBT young adults in bars and nightclubs in a single market [23] and young adults who are at a higher risk for smoking and alcohol use in a number of markets in the United States [24][25][26][27][28].…”
Section: Comparison With Prior Workmentioning
confidence: 91%
“…One strategy that researchers use to recruit young adults involves conducting intercept interviews in social venues (eg, bars, nightclubs) where the target population spends time. A number of researchers have used this strategy to recruit young adults who are at a higher risk for smoking and alcohol use [24][25][26][27][28]. Furthermore, Fallin and colleagues used this strategy to successfully recruit LGBT young adults in bars and nightclubs [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation